Integrasi Pengetahuan, Religiusitas, Promosi Dan Minat Dalam Keputusan Menabung Berbasis Perilaku Individu: Pendekatan Multidisiplin (MSDM, Psikologi, Perbankan Syariah, dan Akuntansi) - Erna Sipahutar; Siti Kadariah; Alim Murtani; Putri Nazli; Meitiya Trihapsari; Hasby Asshidiq (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the integration of knowledge, religiosity, promotion, and intention in influencing saving decisions based on individual behavior using a multidisciplinary approach. This approach integrates the perspective of Human Resource Management (HRM) as the primary framework in understanding individual behavior, supported by psychology in explaining intention and decision-making processes, Islamic banking in examining religiosity aspects, and accounting in explaining financial knowledge. This study employs a quantitative method with a survey design, where data are collected through questionnaires distributed to respondents who are prospective or existing customers of financial institutions. The analysis technique used is Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to examine the relationships among variables as well as the role of intention as an intervening variable. The results indicate that knowledge, religiosity, and promotion have a positive and significant effect on saving intention. Furthermore, intention is found to have a significant effect on saving decisions. In addition, intention also acts as a mediating variable in the relationship between knowledge, religiosity, and promotion on saving decisions. These findings suggest that saving behavior is influenced not only by rational factors but also by values, motivation, and external stimuli integrated within individual behavior. This study provides theoretical contributions to the development of individual behavior studies within HRM in a financial context, as well as practical contributions for financial institutions, particularly Islamic banks, in designing strategies to enhance public saving intention and decisions. Keywords: knowledge, religiosity, promotion, intention, saving decision, individual behavior, multidisciplinary